2012
DOI: 10.4103/2277-9175.100140
|View full text |Cite
|
Sign up to set email alerts
|

Study of C reactive protein as a prognostic marker in malaria from Eastern India

Abstract: Background:C-reactive protein (CRP) is useful as marker of severity in malaria. African studies have shown that serum CRP levels correlate with parasite burden and complications in malaria, especially falciparum. However, there are very few data on CRP levels in Indian malaria patients.Materials and Methods:We assessed CRP levels in malaria patients at presentation and studied for any relation of CRP levels with subsequent prognosis. Statistical tests included student's t-test, Mann Whitney U test, and chi squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
39
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 12 publications
10
39
1
Order By: Relevance
“…Also patients who were admitted had higher CRP levels than patients who were treated on OPD basis. Similar findings were observed by Paul et al 8 & Bainik Adhikari 11 in their study. In our study, we measured CRP levels only at the time of admission or first contact, However serial measurement of CRP levels, can be even better at assessment of course of the disease.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Also patients who were admitted had higher CRP levels than patients who were treated on OPD basis. Similar findings were observed by Paul et al 8 & Bainik Adhikari 11 in their study. In our study, we measured CRP levels only at the time of admission or first contact, However serial measurement of CRP levels, can be even better at assessment of course of the disease.…”
Section: Discussionsupporting
confidence: 82%
“…Thus, measurement of CRP can be useful in understanding the pathogenesis of severe malaria. 8 The results of the study showed that CRP levels are increased significantly in patients with malarial infection. Also CRP levels were significantly higher in patients with Plasmodium falciparum infection compared to patients with Plasmodium vivax infection.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations